2018
DOI: 10.1029/2017wr020826
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Study of Methane Adsorption onto Partially Saturated Shales

Abstract: Shale gas equilibrates through gas‐liquid‐solid interactions in reservoirs, but the role of moisture is rarely investigated. To determine how adsorbed water influences methane behavior, three carboniferous shale samples from the Qaidam Basin, China, were humidified at five levels up to a relative humidity of 89%, and their methane capacities at pressures up to 12 MPa were studied. The experimental results indicate that two water‐related mechanisms, “water blocking for methane transport” and “surface competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Merkel et al (2015) conducted the similar experiments and arrived at the same conclusions reported by Gasparik et al (2013). Wang et al (2018) investigated the influences of water on methane adsorption in three partially saturated shales. They found that a hint of water affects the methane adsorption less in samples with lower water contents and when the water content is increased, water clearly impedes methane adsorption.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Merkel et al (2015) conducted the similar experiments and arrived at the same conclusions reported by Gasparik et al (2013). Wang et al (2018) investigated the influences of water on methane adsorption in three partially saturated shales. They found that a hint of water affects the methane adsorption less in samples with lower water contents and when the water content is increased, water clearly impedes methane adsorption.…”
Section: Introductionmentioning
confidence: 67%
“…Thus, methane adsorption experiments on moisture-equilibrated shale samples were produced. Some researchers carried out equilibrium moisture treatment on rock samples prior to the experiments (Ross and Bustin, 2009;Gasparik et al, 2013;Merkel et al, 2015;Wang et al, 2018;Tian et al, 2020). For example, Ross and Bustin (2009) studied the methane adsorption capacity of shale under moistureequilibrated condition and reported a 20-90% reduction compared to the value under dry condition.…”
Section: Introductionmentioning
confidence: 99%
“…S i decreases with increasing methane pressure from 0.1 to 5 MPa. Previous studies on gas adsorption in shales have indicated that the adsorption capacity of shale rocks increases with increasing gas pressure and that the adsorbed gas may account for more than 50% of the total gas storage . More methane molecules are adsorbed onto the pore surface of the sample with increasing methane pressure, resulting in the wettability of the pore surface changing from water-wet to oil-wet.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors contributing to the adsorption amount have been reported to date (for example, ref ). According to previous experimental studies, total organic carbon (TOC), thermal maturity, and clay content ,, are positively correlated with the adsorption amount, while temperature and moisture content , have a negative correlation with the adsorption amount.…”
Section: Introductionmentioning
confidence: 92%